Reliable scalable video streaming using layer weight switching‐based unequal Luby transform. Issue 5 (1st March 2016) - Ha, H.; Ryu, E.‐S.
Abstract : A layer weight switching‐based unequal Luby transform (LWS‐ULT) method is proposed to minimise video distortion over packet‐lossy networks. The proposed ULT method divides all quality layers into more important set (MIS) and less important set to provide unequal packet protection property in LT codes based on error propagation effects. The number of quality layer in MIS is adjusted in accordance with channel status. At high packet loss rate, lower number of quality layer is assigned into MIS for more protection of quality layer with larger error propagation weight. On the other hand, higher number of quality layer is included in MIS for improving video quality by expanding the range of protection at low packet loss rate. Simulation results demonstrate that the proposed LWS‐ULT method gives robust performance and significantly improved video quality (0.9–1.2 dB in Y‐PSNR), compared with the conventional ULT schemes.